1961
DOI: 10.1099/00221287-26-3-509
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and Cross-resistance of Escherichia coli Mutants to Antitumour Agent Mitomycin C

Abstract: SUMMARYThe cross-resistance patterns are described for 96 mutants selected in one step from Escherichia coli strain S for resistance to Mitomycin C. The test agents used were ultraviolet radiation, seven radiomimetic and two non-radiomimetic compounds. Seven different types of mutants could be selected in one step from the parent. Five of these were radioresistant; two were chemoresistant. Of the radioresistant types two were identical with types previously isolated using other radiomimetic agents for selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1965
1965
1988
1988

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Biochemical and genetic evidence suggest that the pathways which repair DNA damaged either by UV or by MC in Escherichia coli (3,38,44,45), Micrococcus radiodurans (33,34), and Bacillus subtilis (12) share at least some common gene functions. One consequence of overlapping repair pathways is that bacteria which are resistant to UV are often resistant to MC (3,14,33). Accordingly, we investigated whether such a positive correlation exists between UV and MC sensitivity among the Leptospira spp.…”
mentioning
confidence: 99%
“…Biochemical and genetic evidence suggest that the pathways which repair DNA damaged either by UV or by MC in Escherichia coli (3,38,44,45), Micrococcus radiodurans (33,34), and Bacillus subtilis (12) share at least some common gene functions. One consequence of overlapping repair pathways is that bacteria which are resistant to UV are often resistant to MC (3,14,33). Accordingly, we investigated whether such a positive correlation exists between UV and MC sensitivity among the Leptospira spp.…”
mentioning
confidence: 99%
“…It causes preferential inhibition of deoxyribonucleic acid (DNA) synthesis (22), degradation of DNA during post-treatment incubation (3,16,25), and induction of temperate phage (13,15,17). It also has a crossresistance relationship with UV irradiation (3,6,16). MTC is known to cause the formation in vivo and in vitro of a cross-linked DNA (9,10), whereas UV irradiation causes the formation of thymine dimers in DNA (4,21).…”
mentioning
confidence: 99%
“…Mutations that determine resistance to the mitomycins are chromosomally-localizable in B. subtilis and clustered in the early-replicating segment of the genome, which bears genetic loci for streptomycin and erythromycin resistance, and for ribosomal and transfer RNAs (IYER, 1966). Although the biochemical basis of mitomycin resistance is not known at present, the above results together with the known pleiotropic effects of mitomycin resistance (GREENBERG et al, 1961; lYER, 1966), and mitomycin effects on ribosomal function (SuzuKI and KILGORE, 1964), suggest that mitomycin resistance might be related to the latter function (IYER, 1966) or to some general permeability barriers. It might be of interest to mention a report by YosHIOKA and KuNII 220 W. SzYBALSKI and V. N. !YER: (1966}, who observed that mitomycin-resistant streptococcus mutants produced a mitomycin-inactivating factor.…”
mentioning
confidence: 77%
“…In the case of mitomycin-resistant E. coli, a lower degree of in vivo cross-linking was observed than in the corresponding sensitive mutant strains (IYER and SzYBALSKI, 1963). As discussed earlier, the cross resistance between mitomycin and radiation observed with some resistant strains (GREENBERG et al, 1961;GREENBERG and WOODY-KARRER, 1963) is most probably related to the similar repair mechanisms observed for UV or mitomycin damaged DNA (BoYcE and HowARD-FLANDERS, 1964;HowARD-FLANDERS et al, 1966). The temperature reactivation of mitomycin-exposed cells (WINKLER, 1962 a and b) could also be interpreted by involving the differential effect on the repair mechanism: temporary inhibition of DNA synthesis at high temperature permits the effective elimination of mitomycin-modified bases.…”
mentioning
confidence: 78%